Review of Human Resource Management in the Field of Public Management and Public Administration - Haerah, Kahar (Sahabat Publikasi, 2024)
The goal of this research is to elevate the importance of Human Resources Management within public management and administration. Many empirical studies published in academic journals between 2000 and 2019 corroborate this aim. The study's outcomes underscore variations among different disciplines and pinpoint shortcomings in particular nations. Furthermore, the findings provide directions for future research endeavors, proposing alternative theories, frameworks, research methodologies, and approaches to enhance the pertinence of Human Resources Management research in public sector contexts.